Individuals hospitalized with acute mania have increased exposure to antimicrobial medications. (17th July 2016) - Yolken, Robert; Adamos, Maria; Katsafanas, Emily; Khushalani, Sunil; Origoni, Andrea; Savage, Christina; Schweinfurth, Lucy; Stallings, Cassie; Sweeney, Kevin; Dickerson, Faith
Abstract : Objectives: We have preciously documented that many individuals with acute mania have immune activation. However, the sources of immune activation have not been identified. We investigated whether individuals hospitalized with acute mania have evidence of bacterial infections as determined by the prescription of systemic antimicrobial agents. Methods: We assessed the recent prescription of systemic antimicrobial medications and the site of presumed bacterial infection in 234 individuals hospitalized for acute mania in either an inpatient unit or a day hospital. We also assessed individuals hospitalized for other psychiatric disorders (n=368) and controls (n=555). We employed logistic regression models to compare the rates of antibiotic prescription in individuals with the different diagnoses, employing demographic variables as covariates. Results: We found that individuals hospitalized with acute mania had a substantially increased rate of recent antimicrobial prescription, defined as exposure within three days of ascertainment (adjusted odds ratio=5.5, 95% confidence interval: 2.2–14.1, P <.0002). Overall, a total of 18 of the 234 (7.7%) individuals hospitalized for acute mania were prescribed antibiotics as opposed to seven of 555 (1.3%) controls. The prescription of antibiotics was associated with being on an inpatient unit as opposed to being in the day hospital, and having increased mania symptom severity but not with other clinical ratings, demographic variables, or psychiatric medications. Hospitalization for other psychiatric disorders was not associated with the recent prescription of antimicrobial medications. The urinary tract was the most common site of infection in women, while the respiratory tract and mucosal surfaces were the most common sites in men. Conclusions: Individuals hospitalized with acute mania have a markedly increased rate of bacterial infections, as evidenced by the recent prescription of antimicrobial agents. The prevention and effective treatment of bacterial infections may be important interventions for the management of individuals with mania. Abstract : Editor Highlight: Previous studies have shown that many individuals hospitalized for episodes of mania have evidence of immune activation; however, the source of the immune activation has not been previously identified. The authors found that individuals hospitalized for mania had a significantly increased rate of recent bacterial infections compared to controls and individuals hospitalized for other psychiatric disorders as evidenced by their receipt of antimicrobial medications. The control of infections and antimicrobial therapy should be explored as means to prevent episodes of mania